Computer Assessment Test at the Association of Indonesian Independent Housing Experts with Waterfall Model - Elin Panca Saputra; Risqi Nur Alfiyah; Indriyanti Indriyanti (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The Association of Indonesian Self-Help Housing Experts (PERAPSI) is a government organization that was just inaugurated in 2020 with an official certificate from the Ministry of Law and Human Rights of the Republic of Indonesia (KEMENKUMHAM) under the Directorate of Public Housing, Ministry of Public Works and Public Housing (PUPR).The Association of Indonesian Self-Help Housing Experts (PERAPSI) is tasked with directly gathering people in remote parts of the archipelago, an estimated 4,500 people who are not recorded by the Ministry of PUPR who are working on building self-help houses.For this reason, the Association of Indonesian Self-Help Housing Experts (PERAPSI) itself will record data and go through a process of data collection and assessment of people who are not recorded.The assessment process itself is through the Computer Assessment Test (CAT).The system development method used is the Waterfall method.Methods of Requirement Definition, System and Software Design, Construction, Deployment, which ends with support for the resulting software.With this designed system, it is a test with a computer in real time.This system can provide several advantages compared to the currently running system, namely efficiency and effectiveness in processing information and managing computer test data.